Identifikasi Aktivitas Petani Dan Sifat Fisik Tanah Sawah Di Desa Detusoko Barat Kecamatan Detusoko Kabupaten Ende - Martinus Putra Jayawora; Charly Mutiara (AGRICA, 2020)
This study aims to determine the activity of farmers and the physical properties of soil on rice fields in the village of Detusoko Barat, Detusoko District, Ende Regency. The research method used is the method of purposive sampling. The research was carried out in paddy fields in the village of Detusoko Barat and in the soil chemical laboratory of the Faculty of Agriculture, Undana. Farmer activity variables observed were rice cultivation such as seedbed, land preparation, planting, fertilizing, maintaining, harvesting. Variable physical characteristics that are analyzed temperature, rainfall, humidity, drainage, texture, effective depth, slope, surface rock, rock outcrop. The results showed that the activities of farmers in the village of West Detusoko carried out rice cultivation twice a year, tillage using a tractor and fertilizing using inorganic fertilizer. The physical properties of soil in the ciherang rice variety in Detusoko Barat village are generallyclassified as very suitable (S1) class. And in rice varieties, Bengawan also generally belongs to the (S1) class very appropriate.